PHYSIOLOGICAL EFFECT OF RAJYOGA MEDITATION ON CHRONIC TENSION HEADACHE AND ASSOCIATED CO-MORBIDITIES - ., Kiran; Girgla, Kawalinder K; Chalana, Harsh; Singh, Harjot (Pakistan Journal of Physiology, 2016)
Background: Stress is the most common factor which causes Chronic Tension Headache (CTH). Yoga and Meditation are non-pharmacological therapies for the treatment of stress. This study aimed to evaluate the effect of Rajyoga meditation on CTH and related co-morbidities. Methods: One hundred patients having CTH were short listed for the study based on the International Headache Society Criteria II. Study group patients were taught Rajyoga meditation. Visual pain analogue scale (VAS) was used to assess the intensity of headache, before and after meditation. Anxiety and depression were assessed by Hamilton anxiety and depression scales. Student’s t-test was used to compare the basal values for all the quantitative parameters between the two groups, and p<0.05 was taken as significant. Results: There was highly significant (p<0.001) reduction in intensity of pain in meditators. After 8 weeks, relief of headache in study group was 87% and it was 23% in control group. The improvement in frequency of headache was 86% in meditators and 23% in control group. The improvement in duration of headache was 93% in meditators and 32% in control group. Mean relief of Headache Index was 95% in meditators, whereas it was 34% in control group. The relief in anxiety was 92% in meditators and 34% in controls. Depression scores showed improvement up to 87% in meditators and 38% in control group. Conclusion: Rajyoga Meditation helps in decreasing stress hence reducing CTH and associated co-morbidities. Rajyoga meditation can be used as an adjunct to traditional therapy in management for CTH where co-morbidity is a major complication. Pak J Physiol 2016;12(2):22–5